Is Osteoarthritis Always Associated with Low Bone Mineral Density in Elderly Patients? - Bojana N. Stamenkovic; Natasa K. Rancic; Mila R. Bojanovic; Sonja K. Stojanovic; Valentina G. Zivkovic; Dragan B. Djordjevic; Aleksandra M. Stankovic (Medicina, 2022)
Background and Objectives: The relationship between osteoarthritis (OA) and osteoporosis (OP) has been analysed for over four decades. However, this relationship has remained controversial. Numerous observational and longitudinal studies have shown an inverse association between the two diseases and a protective effect of one against the other. On the other hand, some studies show that patients with OA have impaired bone strength and are more prone to fractures. The study’s main objective was to determine the bone mineral density (BMD) of the spine and hip (femoral neck) of postmenopausal women of different ages, with radiologically determined OA of the hip and knee, as well as to determine the correlation between BMD values and age in the experimental group. Materials and Methods: The retrospective cohort study included 7018 patients with osteoarthritis of peripheral joints and the spine, examined by a rheumatologist in an outpatient rheumatology clinic at the Institute for Treatment and Rehabilitation, Niška Banja from July 2019 to March 2021. A nested anamnestic study was conducted within the cohort study of patients, and it included two groups: an experimental group composed of 60 postmenopausal women, and a control group composed of the same number of women. Out of 120 patients, 24 did not meet the criteria for the continuation of the study (due to technical errors—radiographic and/or densitometry artefacts). Fifty-six postmenopausal women (aged 45–77 years) with hip and knee radiological OA were examined as an experimental group. The participants were divided into two subgroups according to age (45–60 years and over 61 years). The control group included 40 healthy postmenopausal women of the same age range, without radiological OA, with normal BMD of the hip and spine. All patients with OA met the American College of Radiology (ACR) criteria. OA of the hip and knee was determined radiologically according to Kellgren and Lawrence (K&L) classification, and patients were included in the study if a K&L grade of at least ≥ 2 was present. Hip and spine BMD was measured by dual-energy X-ray absorptiometry (DXA). Results: Compared to the control group, we found statistically significantly lower BMD and T-scores of the spine in older postmenopausal women: BMD (g/cm2), p = 0.014; T-score, p = 0.007, as well as of the hip: BMD (g/cm2), p = 0.024; T-score p < 0.001. The values of BMD and T-score of the spine and hip are lower in more severe forms of OA (X-ray stage 3 and 4, according to K&L), p < 0.001. We found negative correlation between BMD and T-score and age only for the hip: BMD (g/cm2), ρ = 0.378, p = 0.005; T-score ρ = −0.349, p = 0.010. Conclusions: Older postmenopausal women with radiographic hip and knee OA had significantly lower BMD of the hip and spine as compared to the control group without OA, pointing to the need for the prevention and treatment of OA, as well as early diagnosis, monitoring, and treatment of low bone mineral density.